Elevated-temperature tensile deformation and fracture behavior of particle-reinforced PM 8009Al matrix composite - Shuang Chen; Guoqiang Chen; Pingping Gao; Chunxuan Liu; Anru Wu; Lijun Dong; Zhonghua Huang; Chun Ouyang; Hui Zhang (Bulletin of the Polish Academy of Sciences: Technical Sciences, 2021)
Tensile tests of 8009Al alloy reinforced with SiC and Al₂O₃ particles fabricated by powder metallurgy (PM) were conducted at temperatures of 250–350°C and strain rates of 0.001–0.1 s⁻¹. The ultimate tensile strength and yield strength of the samples decreased while the temperature and strain rate increased. The elongation slightly decreased at first and then increased with growing temperature because of the medium-temperature brittleness of the alloy matrix. When the strain rate was 0.1 s⁻¹, the elongation of the 8009Al/Al₂O₃ composites always decreased with an increase in temperature because of the poorly coordinated deformation and weak bonding between the matrix and Al₂O₃ particles at such a high strain rate. The work-hardening rates of the composites sharply increased to maxima and then decreased rapidly as the strain increased. Meanwhile, the 8009Al/SiCₚ composites displayed superior UTS, YS, elongation, and work-hardening rates than those of the 8009Al/Al₂O₃ composites under the same conditions. Compared to 8009Al alloys reinforced with spherical Al₂O₃ particle, 8009Al alloys reinforced with irregular SiC particles exhibited a better strengthening effect. The fracture mechanism of the 8009Al/SiCₚ composites was mainly ductile, while that of the 8009Al/Al₂O₃ composites was primarily debonding at the matrix–particle interfaces in a brittle mode.